Educational strategy in patients with chronic heart failure (Research, Society and Development, 2022)
Heart failure (HF) is considered a serious public health problem whose high prevalence is associated with population aging and improvements in treatment. This study aimed to evaluate the impact of an educational strategy on quality of life and adherence to outpatient treatment of patients with chronic heart failure. This is a randomized clinical study, divided into intervention (IG) and control (CG) groups by means of simple random sampling. All data were analyzed using STATA 14.0 and the significance level of p